Emergency Peripartum Hysterectomy: Results From the Prospective Nordic Obstetric Surveillance Study (NOSS). Issue 2 (June 2016) - Jakobsson, M.; Tapper, A.M.; Colmorn, L.B.; Lindqvist, P.G.; Klungsøyr, K.; Krebs, L.; Børdahl, P.E.; Gottvall, K.; Källén, K.; Bjarnadóttir, R.I.; Langhoff-Roos, J.; Gissler, M.
Abstract : ( Acta Obstetricia et Gynecologica Scandinavica. 94 (2015) 745–754) When hemorrhage is so severe and uncontrollable that it threatens the life of a parturient, an emergency peripartum hysterectomy may be performed. Emergency hysterectomies are used only after conservative treatments have failed and are the last option to prevent maternal morbidity or even death.